The Role of Counselors in Building Student Ethics and Aesthetics in Schools - Puji Gusti Handayani; Dedi Effendi; Yeni Karneli (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The global pandemic and advances in information technology have created new challenges in education, particularly in the development of students' ethics and aesthetics. School counselors play a crucial role in shaping students' character through effective guidance and counseling. This study aims to explore the role of counselors in the development of students' ethics and aesthetics in schools. The method used is a literature review, analyzing various sources related to guidance and counseling and the development of moral and aesthetic values in students. The findings indicate that effective interventions by counselors can shape students' ethical attitudes and aesthetic understanding, as well as highlight the importance of collaboration between counselors, teachers, and parents. The use of technology in guidance and counseling has also proven effective in supporting students' character development. Therefore, collaboration among all educational stakeholders and the development of counselor competencies are key factors in creating quality education. These efforts can lead to a more holistic approach to education, fostering an environment where students are not only academically successful but also socially responsible and culturally aware. By prioritizing these partnerships and professional development, schools can cultivate well-rounded individuals prepared to navigate the complexities of modern society.